The degree of suitability of the organizational climate in Yemeni private universities from the point of view of academic and administrative leaders in these universities - Al-Aush, Ashwaq Yahya Yahya; Maghrabah, Fahd Saleh Qasem (Journal of Educational and Psychological Sciences, 2024)
The study aimed to assess the suitability of the organizational climate in Yemeni private universities from the perspectives of academic and administrative leaders in these universities. The researchers employed a descriptive survey method, using a questionnaire consisting of 17 statements divided into three dimensions. The questionnaire was distributed to a purposive sample of 289 leaders in 12 universities. The study findings revealed that the level of availability of organizational climate in Yemeni private universities was generally high, with an average score of 3.56 out of 5. In terms of the main dimensions, communication ranked first, followed by organizational structure, and work nature came third, with all dimensions showing a high level of suitability. The results also indicated statistically significant differences (α≤0.05) in the perspectives of the sample based on the gender variable, with males holding different views. However, no significant differences were found based on variables such as job position, employment level, educational qualification, and years of service. Based on the results of the study, the researchers recommended improving the nature of the work of employees in private universities, preserving distinguished employees to enhance the sustainability of competitive advantage, and continuing to pay attention to information and communications technology, in addition to proposals for complementary studies on the subject.
Keywords: Organizational climate; Administrative leaders; Academic leaders; Yemeni private universities